Stratospheric Sulfate Aerosols Impacts on West African Monsoon Precipitation Using GeoMIP Models - Bonou, Frédéric; DA ALLADA, Y. Casimir; BALOÏTCHA, EZINVI (My University, 2023)
Stratospheric Aerosol Geoengineering (SAG) is proposed to offset global warming; however, the use of this approach can an impact on the hydrological cycle. We used simulations from Coupled Model Intercomparison Project (CMIP5) and Geoengineering Model Intercomparison Project (G3 simulation) to analyze the impacts of SAG on precipitation (P) and to determine its responsible causes in West Africa and Sahel region. CMIP5 historical data were first validated, the results obtained are consistent with observational data. Under the Representative Concentration Pathway scenario RCP4.5, a slight increase is found in the West Africa Region relative to present-day climate. The dynamic processes especially, the monsoon shifts are responsible for this precipitation change. Under RCP4.5, during the monsoon period, reductions in P are 0.86%, 0.80% relative to the present-day climate in the Northern and Southern Sahel, respectively, while precipitation is increased by 1.04% in the West African Region. Under SAG, we find a 3.71% decrease of precipitation in the West African Region while the precipitation decrease is 17.4% and 8.47% respectively in the North Sahel and South Sahel. This decrease in monsoon precipitation is mainly explained by changes in dynamics, which lead to weakened monsoon circulation and a shift in the distribution of monsoon precipitation. This result suggests that SAG deployment to balance all warming can be harmful to rainfall in WAR if the amount of SO2 to be injected into this tropical area is not taken into consideration.
Keywords: West Africa; monsoon precipitation; climate change; geoengineering; GeoMIP; G3; RCP4.5